Pengaruh Return On Equity Dan Net Profit Margin Terhadap Harga Saham Pada PT Mayora Indah Tbk Periode 2013 – 2022 - Ebbyh Rukli; Faisal Faisal (Jurnal Nuansa : Publikasi Ilmu Manajemen dan Ekonomi Syariah, 2024)
This research aims to find out the influence of Return On Equity (ROE) and Net Profit Margin (NPM) on stock prices. The independent variables used are Return On Equity (ROE) and Net Profit Margin (NPM) and the dependent variable used is Share Price. This research method is associative with a quantitative approach. The sample in this research is the annual financial report of PT Mayora Indah Tbk for the 2013-2022 period. A total of 10 data can be processed. Data were tested using descriptive statistical test methods, classical assumption tests (normality test, multicollinearity test, heteroscedasticity test, and autocorrection test), multiple linear regression analysis, coefficient of determination test and hypothesis test (T test and F test) with a significance level of 5%, then the data was processed using IBM SPSS Statistics Version 25. The results of this research show that partially the Return On Equity (ROE) variable has a negative and significant effect on stock prices. The research results based on the results of the t test (partial test) show that the calculated t value > t Table -3.179 > 2.365 and the significance value is 0.016 < 0.05 so Ho is rejected and Ha is accepted. Partially, the Net Profit Margin (NPM) variable has a positive and significant effect on share prices. The research results based on the results of the t test (partial test) show that the calculated t value > t table value or 3.216 > 2.365 and seen from the significance value of 0.015< 0.05, so Ho is rejected and Ha is accepted . Simultaneously the variables Return On Equity (ROE) and Net Profit Margin (NPM) variables have a significant effect on share prices. The research results based on the F test (simultaneous test) the value of Fvalue > Ftable or 5.360 > 4.737 with a significance value of 0.039 < 0.05, so Ho is rejected and Ha is accepted. The Result of testing the coefficient o0f determination can be concluded that the two independent variables influence stock price by 49.2% while the remaining 50.8% is influenced by other factors not examined in this research.